Interacting The Urban Masterplan of Unicamp with the Sustainable Development Goals - Thalita S. Dalbelo (Journal of Sustainability Perspectives, 2021)
Universities are the training centers for future decision-makers in the social, political and economic sectors. Considering the university campus as an urban locus or even a microcosm of society, the change that begins in the urban planning of a university is an opportunity for example and replication in the city. This paper presents the development of the Unicamp Urban Masterplan, a strategic project of the university that involves the participation of all-around social actors: professors, students, researches, staff and local community and brings the actual panorama, the future scenarios and the guidelines to achieve them. It is organized through six planning areas: 1. Urban usage and heritage; 2. Environment; 3. Urban infrastructure; 4. Mobility and accessibility; 5. Social interaction; and 6. University and society. Projects resulting from these guidelines should be developed through living laboratories. Campus territories and their evolution are monitored through performance indicators aligned with the UI GreenMetric sustainable university ranking process indicators. This paper explains the methodology in which the urban projects be implemented through living laboratories to put into practice the SDGs, as necessary action for the transition to sustainability in the campuses. The use of the university campuses as a living laboratory results in the transformation of the Unicamp space and impel the replication to transform the local community to sustainability and to disseminate solutions to the cities and other universities